"I Think I Have Enough for Now": Living with COVID-19 Antibodies in the Philippines. Issue 5 (4th July 2022) - Lasco, Gideon
ABSTRACT: Drawing on face-to-face and virtual fieldwork in the Philippines, I document the emergence of antibody testing as a popular practice among Filipinos during the COVID-19 pandemic, helping them make decisions about vaccines and other life choices. Antibodies gave people a sense of agency and control amid a health crisis for which political and medical authorities failed to offer certainty and hope, particularly at a time of vaccine scarcity and viral surges. However, by diverting attention from the health care system to individual immune systems, antibodies also reinforced the individual "responsibilization" that has characterized the Philippine government's pandemic response.